ChemInform Abstract: anti‐Selective Asymmetric Henry Reaction Catalyzed by a Heterobimetallic Cu—Sm—Aminophenol Sulfonamide Complex. Issue 34 (4th August 2016) - Li, Yang; Deng, Ping; Zeng, Youmao; Xiong, Yan; Zhou, Hui
Abstract: The title reaction between aryl, hetaryl, or alkenyl aldehydes and nitromethane or nitroethane proceeds with very high anti‐selectivity and very high enantioselectivity.